Significance of 1,3,4-Oxadiazole Containing Compounds in New Drug Development - Rana, Kavita; Salahuddin; Sahu, Jagdish K. (Current Drug Research Reviews, 2021)
Background: Oxadiazole core displays various pharmacological properties among five membered nitrogen heterocyclic compounds, specially 1,3,4-oxadiazole containing molecules that have occupied a particular place in the field of synthetic medicinal chemistry as surrogates (bioisosteres) of carboxylic acids, carboxamides and esters. Moreover, they are having widespread kind of applications in numerous zones as polymers, as luminescence producing materials and as electron- transporting materials and corrosion inhibitors. Methods: This study contains comprehensive and extensive literature survey on chemical reactivity and biological properties associated with 1,3,4-oxadiazole containing compounds. Results: This review summarises 1,3,4-oxadiazole moiety in numerous compounds with reported pharmacological activity such as antiviral, analgesic and anti-inflammatory, antitumor, antioxidant, insecticidal and anti-parasitic, etc. Nevertheless, ring opening reactions of the 1,3,4-oxadiazole core have also made great attention, as they produce new analogues containing an aliphatic nitrogen atom and to other ring systems. Conclusion: In relation to the occurrence of oxadiazoles in biologically active molecules, 1,3,4- oxadiazole core emerges as a structural subunit of countless significance and usefulness for the development of new drug aspirants applicable to the treatment of many diseases. It concludes that 1,3,4-oxadiazole core compounds are more efficacious and less toxic medicinal agents with respect to new opinions in the search for rational strategies.
Keywords: anti-tubercular